KONFLIK SOSIAL DALAM NOVEL ORANG-ORANG PROYEK KARYA AHMAD TOHARI - Mulyani, wahyu; Sarujin (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2022)
The research method uses descriptive qualitative, sociological approach. The source of the novel People Project by Ahmad Tohari. Watch, tap and record data collection. Analysis of information presentation data. The results of social class conflicts in the novel Orang-Orang Project by Ahmad Tohari. there is a stark difference between bourgeois society and proletarian society. The difference lies in the socioeconomic level. Because the novels of project people were written by Ahmad Tohari during the New Order era, which still used the capitalist system, so that the bourgeois society became the ruler, because they had a lot of capital or wealth, while the proletarian society was often deceived by the bourgeois society because it was poor. Socio-political conflicts in the novel People Project by Ahmad Tohari. involving community leaders, political parties, and officials.